Composition and creativity in the elementary music class - Lackey, Samantha (Kansas State University, 2022)
After my kindergarten learned how to read and count stick notation, students got to create their own rhythms on the whiteboard. We used these rhythms as an ostinato while we sang a scale and built up to using them while singing a song. To help us keep a steady beat, we played a game to the tune Acka Backa. Once they learned Acka Backa, we used glockenspiels to keep a beat. This year I have had a major shift in my career from 5-12 to Elementary music. Even though my Masters’ work has been in instrumental music, I feel so much more organized. I can plan my lessons more effectively and utilize a lot of play-based learning now. My communication to parents has improved as well. I started using Happy Notes to give to students in class. These notes can be for anything good I see that I want to encourage and reinforce. For example, some of the notes I have given out have been for good posture while singing or playing the recorder, for being an active listener, raising their hand quietly, taking good care of instruments, and being a positive example. In addition to these notes, I take a picture of the student holding the note and send it to the family on SeeSaw. I also post videos from class occasionally and have even shared articles during Music In Our Schools Month. We read Leadership Lessons by Bill Snyder (Shoop & Scott, 1999) that gave me a lot of enthusiasm to do a much better job at goal setting. Through this, I have been focusing more on the steps to achieve the goals rather than the goal itself. I try to help the students see and identify their progress. One of my first grade classes is especially difficult due to unregulated emotions and lack of physical self-control. When we have a class period without major issues, I make sure to convey several praises to all students, and especially those who may struggle at other times, to reinforce those behaviors. Prior to beginning my Masters’, I was heading towards burnout. Lack of administrative support, other staff members that would talk poorly on our program and try to pit students against music, a counselor actively recruiting students out of music into study hall, and poor scheduling were some of the reasons I was heading down this dark spiral. Through these classes and the switch in my career, I am happier than ever. I began to see the reason why I became a teacher and how big of an impact I can leave on these students’ lives. These classes have helped me learn how to be much more organized and truly enjoy my time teaching the students.
Keywords: Music composition; Elementary music; Creativity in elementary music